The Influence of Transformational Leadership Style and Compensation on Teacher Performance through Organizational Commitment as an Intervening Variable - Soelistya, Djoko; Selamet, Selamet (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to determine the influence of transformational leadership style and compensation on teacher performance with organizational commitment as an intervening variable in the Malik Ibrahim Gresik Islamic Foundation Educational Institution. The quantitative approach uses a saturated sampling method, where the entire population is sampled. Data was collected through a questionnaire given to teachers at the institution and then analyzed using path analysis techniques to test the relationship between variables. The results of the study show that transformational leadership style has a significant influence on teacher performance. The better the transformational leadership style implementation, the higher the teachers' performance. On the other hand, compensation does not significantly influence teacher performance, which means that the increase in compensation does not directly impact improving teacher performance. However, through organizational commitment as an intervening variable, it was found that organizational commitment plays an important role in mediating the influence of transformational leadership style on teacher performance. These results show that teacher performance can be improved through transformational leadership and increased organizational commitment. This research provides practical implications for the management of educational institutions, especially in developing transformational leadership styles and strengthening organizational commitment to improve teacher performance.